The Effectiveness of the Implementation of Restorative Justice in Resolving Minor Criminal Offenses in Indonesia - Siti Fatimah; Ermanita Permatasari; Septiani Selly Susanti (VRISPRAAK : International Journal of Law, 2026)
This study examines the effectiveness of restorative justice (RJ) implementation in resolving minor criminal cases in Indonesia, with particular reference to Supreme Court Regulation Number 1 of 2024 and its predecessor Regulation Number 2 of 2012. Employing a normative-empirical legal research method, this paper analyzes primary legal materials, secondary literature, and court decision data from 2019 to 2023. The findings indicate that restorative justice has demonstrated significant potential in reducing recidivism rates, alleviating court backlog, and restoring harmonious social relationships between offenders and victims. However, implementation challenges persist, including inconsistent judicial interpretation, limited institutional capacity, and insufficient community participation. This study argues that a systemic legal reform encompassing legislative consolidation, judicial training, and community empowerment is indispensable for maximizing the effectiveness of restorative justice in Indonesia’s criminal justice system.